Family transactions and relapse in bipolar disorder. - Rosenfarb, I; Miklowitz, D; Goldstein, M; Harmon, L; Nuechterlein, K; Rea, M (2001)
This study examined whether patient symptoms and relatives' affective behavior, when expressed during directly observed family interactions, are associated with the short-term course of bipolar disorder. Twenty-seven bipolar patients and their relatives participated in two 10-minute family interactions when patients were discharged after a manic episode. Results indicated that patients who showed high levels of odd and grandiose thinking during the interactions were more likely to relapse during a 9-month followup period than patients who did not show these symptoms during the family discussions. Relapse was also associated with high rates of harshly critical and directly supportive statements by relatives. Patients' odd thinking and relatives' harsh criticism were significantly more likely to be correlated when patients relapsed (r = .53) than when they did not relapse (r = .12). Results suggest that bipolar patients who show increased signs of residual symptomatology during family transactions during the post-hospital period are at increased relapse risk. The data also suggest that relatives of relapsing patients cope with these symptoms by increasing both positive and negative affective behaviors. Moreover, a bidirectional, interactional relationship between patients' symptoms and relatives' coping style seems to capture best the role of the family in predicting relapse in bipolar disorder.